2018
DOI: 10.1165/rcmb.2017-0364oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled TRIM72 Protein Protects Ventilation Injury to the Lung through Injury-guided Cell Repair

Abstract: Studies showed that TRIM72 is essential for repair of alveolar cell membrane disruptions, and exogenous recombinant human TRIM72 protein (rhT72) demonstrated tissue-mending properties in animal models of tissue injury. Here we examine the mechanisms of rhT72-mediated lung cell protection in vitro and test the efficacy of inhaled rhT72 in reducing tissue pathology in a mouse model of ventilator-induced lung injury. In vitro lung cell injury was induced by glass beads and stretching. Ventilator-induced lung inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 69 publications
(129 reference statements)
6
26
0
Order By: Relevance
“…Such data argue that TRIM14 acts as a negative regulator of cytosolic DNA sensing through bringing TBK1 and STAT3 together to promote phosphorylation of STAT3 at Ser727. Trim14 KO macrophages were remarkably efficient at limiting M. tuberculosis replication but permissive for vesicular stomatitis virus (VSV), consistent with previous reports (26).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Such data argue that TRIM14 acts as a negative regulator of cytosolic DNA sensing through bringing TBK1 and STAT3 together to promote phosphorylation of STAT3 at Ser727. Trim14 KO macrophages were remarkably efficient at limiting M. tuberculosis replication but permissive for vesicular stomatitis virus (VSV), consistent with previous reports (26).…”
Section: Introductionsupporting
confidence: 91%
“…A previous study demonstrated a similar role for TRIM14 in controlling VSV replication but reported that TRIM14 KO macrophages had lower ISG expression compared to wild-type (26).…”
Section: Loss Of Trim14 Impacts the Ability Of Macrophages To Controlmentioning
confidence: 78%
See 2 more Smart Citations
“…Interestingly, rhMG53 has been very successful in treating ischemia/reperfusion injury and has been also used in the treatment of skeletal muscle [25,26], cardiac muscle [27], and liver tissue [22]. Also, aerosolized rhMG53 has ameliorated the effects of ventilator-induced lung injury [7,28]. These studies introduce the possibility that rhMG53 could be used to increase the repair capacity of other non-muscle cell types like neurons.…”
Section: Introductionmentioning
confidence: 99%